2021
DOI: 10.1111/1751-7915.13773
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Cuscuta campestris‐mediated enrichment system for genomic and transcriptomic analyses of ‘Candidatus Liberibacter asiaticus’

Abstract: Summary ‘Candidatus Liberibacter asiaticus’ (CLas) is a phloem‐limited non‐culturable α‐proteobacterium associated with citrus Huanglongbing, a highly destructive disease threatening global citrus industry. Research on CLas is challenging due to the current inability to culture CLas in vitro and the low CLas titre in citrus plant. Here, we develop a CLas enrichment system using the holoparasitic dodder plant (Cuscuta campestris) as an amenable host to acquire and enrich CLas from CLas‐infected citrus shoots ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…have shown a higher expression level of flagella genes in psyllids than in plants, which is in sharp contrast to what had been observed previously (Yan et al, 2013). The genes motE and flgC were not mapped in citrus also, in addition to fliQ, while flgA, flgB, and fliE had a low expression level (Li et al, 2021), also in agreement with and the mapping analysis shown here.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…have shown a higher expression level of flagella genes in psyllids than in plants, which is in sharp contrast to what had been observed previously (Yan et al, 2013). The genes motE and flgC were not mapped in citrus also, in addition to fliQ, while flgA, flgB, and fliE had a low expression level (Li et al, 2021), also in agreement with and the mapping analysis shown here.…”
Section: Discussionsupporting
confidence: 87%
“…This value falls in the range observed by other authors, such as the mapping of 0.50% of transcriptome reads of the whole body of B. cockerelli against the Lso genome ( Ibanez et al, 2014 ). Transcriptome analysis of Las was comparatively carried out in citrus and in dodder, with read mapping ranging from 0.11% to 1.44%, respectively ( Li et al, 2021 ), while in adventitious citrus roots in culture media and in alimentary canals of D. citri , 0.28% to 2.51% of reads mapped to Las genome ( Zuñiga et al, 2020 ). In contrast, only 0.01% of reads obtained from infected grapevine mapped against the flavescence dorée phytoplasma ( Abbà et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations